2000
DOI: 10.1177/002215540004800103
|View full text |Cite|
|
Sign up to set email alerts
|

Immunocytochemical Localization of Shc and Activated EGF Receptor in Early Endosomes After EGF Stimulation of HeLa Cells

Abstract: SUMMARY After binding of epidermal growth factor (EGF), the EGF receptor (EGFR) becomes autophosphorylated via tyrosine. The ligand-activated receptor is internalized by endocytosis and subsequently degraded in the lysosomal pathway. To follow EGFR activation after EGF stimulation, we generated antisera to the EGFR phosphotyrosine sites pY992 and pY1173. The SH2 region of Shc binds to both these sites. Both antisera identified EGFR after EGF binding and did not crossreact with the unactivated receptor. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…4, D-I). To further confirm the early endosomal localization of HAP1, HeLa cells were treated with Texas Red-conjugated EGF at 37°C for 10 min, under which conditions the internalized EGF proteins were almost exclusively localized to early endosomes (37,38). We observed that most of the HAP1-positive structures contained internalized EGF (Fig.…”
Section: Hap1 Is Localized To Early Endosomes and Overexpression Of Hmentioning
confidence: 61%
“…4, D-I). To further confirm the early endosomal localization of HAP1, HeLa cells were treated with Texas Red-conjugated EGF at 37°C for 10 min, under which conditions the internalized EGF proteins were almost exclusively localized to early endosomes (37,38). We observed that most of the HAP1-positive structures contained internalized EGF (Fig.…”
Section: Hap1 Is Localized To Early Endosomes and Overexpression Of Hmentioning
confidence: 61%
“…However, the interaction of EGFR and RHA was inhibited by EGFR tyrosine kinase inhibitor in HeLa cells (Fig. S6D, Top), in which the level of EGFR expression is normal (1.4 × 10 5 /cell) (35). The impaired association of EGFR with RHA in HeLa cells upon treatment with tyrosine kinase inhibitor is caused by the absence of EGF/EGFR internalization and EGFR nuclear translocation in the presence of EGFR tyrosine kinase inhibitor (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study, EGFR was detected predominantly in clusters around the nonclathrin-coated plasma membrane. 50 EGFR has been shown to influence the level, phosphorylation state and localization of several proteins involved in the formation of or maintenance of tight junctions. These proteins includes ZO-1, ZO-2, ZO-3, cingulin, occludin, connexin43, nectin-2delta, cytoskeletal proteins and vinculin, actin and cadherins.…”
Section: Discussionmentioning
confidence: 99%